An Overview of Synthesis Based Biomedical Applications of Hydroxyapatite Nanomaterials - Bhandari, Netra Lal; Bista, Sunita; Gautam, Tika Ram; Bist, Kabita; Bhandari, Ganesh; Subedi, Sumita; Dhakal, Kedar Nath (Journal of Nepal Chemical Society, 2021)
Hydroxyapatite (HAp) is the mineral phase of animal bones embedded in a collagen-containing organic matrix. It is a naturally optimized material for the physical support of the bones. Synthetic Hydroxyapatite based biomaterials, hence, find wide applications in orthopedics, dentistry, and tissue engineering due to their biocompatibility, bioactivity, osteoconductivity, and similar chemical composition to that of HAp present in animal bones. Different physicochemical synthetic methods and natural biogenic sources have been reported for the synthesis of nano-hydroxyapatite. However, particle size, aspect ratio, and the distribution of HAp in biomaterials have significant effects to use as bone substitutes and implants. This paper has summarized some synthetic methods of preparing nano-HAp from different biogenic approaches. Further, it focuses on some facile synthetic routes of preparing nano-HAp with controlled particle size with higher crystallinity and native bone architectures. This review article aims to correlate some simplistic and cost-effective biosynthetic approaches of nano-HAp, their size-dependent properties characterization, and biomedical applications.